(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2025)
Antimicrobial residues in food products of animal origin represent a significant public health concern that requires careful consideration due to their harmful effects on consumer health. The presence of antibiotic residues in animal-derived food poses challenges for international trade involving animals and their products. Public health issues related to antibiotic residues in food include the emergence and spread of antimicrobial resistance (AMR), allergic reactions, cancer risks, genetic mutations, birth defects, bone marrow damage, and disruption of normal gut microbiota. The indiscriminate use of antibiotics in livestock can lead to residue levels that exceed permissible limits, resulting in adverse health effects for humans. Limiting antibiotic use is crucial for the safety of animal products. This review examines the administration of antibiotics to food animals, the presence of antibiotic residues in animal-origin foods, and the various factors that influence these residue levels in animal-derived food products in developing countries. It underscores the urgent need for improved regulatory control and surveillance of antibiotic use in food-producing animals to ensure public health safety. The findings highlight the importance of strengthening residue monitoring systems, enforcing withdrawal periods, and promoting responsible antibiotic stewardship to reduce contamination in animal-derived foods. Asian Australas. J. Biosci. Biotechnol. 2025, 10(3), 64-76